Discovery of metabolic resistance to neonicotinoids in green peach aphids (Myzus persicae) in Australia. Issue 8 (30th January 2017) - de Little, Siobhan C; Edwards, Owain; van Rooyen, Anthony R; Weeks, Andrew; Umina, Paul A
Abstract: BACKGROUND: Myzus persicae is a serious pest that attacks a broad range of agricultural crops. This species has developed chemical resistance to many insecticides globally, and within Australia resistance to multiple chemical groups has been identified. Resistance to neonicotinoid insecticides has been discovered in several countries, but has not previously been confirmed in Australia. We use biomolecular assays and bioassays on field‐collected populations to investigate neonicotinoid resistance in M. persicae within Australia. RESULTS: Several geographically and genetically distinct populations showed evidence for resistance in bioassays. Genetic markers identified that the mechanism of neonicotinoid resistance in Australia is metabolic resistance through the enhanced expression of a cytochrome P450 gene, CYP6CY3 . CONCLUSION: M. persicae populations in parts of Australia are now resistant to four different insecticide chemical groups, raising concerns about the long‐term management of this pest. While higher copy numbers of CYP6CY3 were seen in all resistant populations, the number of gene copies was not strongly correlated with the level of resistance as determined by LD50 values generated through bioassays. This finding sheds further light on the complexity of the P450 genes in regulating neonicotinoid resistance. © 2016 Society of Chemical Industry